The kiss of the spindle - Allen, Nancy Campbell, 1969- (Shadow Mountain, 2018)
"Dr. Isla Cooper must travel to Port Lucy in Jamaica to locate the witch that placed a spell on her--one that puts her into a death-like sleep every night--before the spell becomes permanent"--Provided by publisher.